A language contact perspective on Indian English phonology. Issue 4 (7th August 2015) - DOMANGE, RAPHAËL
ABSTRACT: The direction taken by research on Indian English (IE) phonology has been largely determined by the 'non‐native' status which is attributed to this variety. Its form is generally considered to be governed by the combined effects of an idealised model serving as the target in acquisition, and transfers from the different language backgrounds of the speakers. This article adopts a different perspective on the issue, and intends to show the crucial importance of acknowledging the diachronic dimension when discussing varieties, native and non‐native alike. It is proposed that features of present‐day IE vowel inventory can be traced back to non‐southern British English input in the dialect formation processes, thus suggesting continuity through time rather than ever‐repeated deviations from the hypothesised target.